(untitled) (Agricultural Engineering, 2018)
The paper presents the results of analysis concerning the impact of temperature on sedimentation in the caustic soda solution that constitute a contamination after the process of cleaning utensils and pipes for hopped wort transport in the brewery. The solution was collected from the production plant after the process of cleaning and subjected to 12-hour sedimentation and changes of the solid particles participation, their size and percentage share in the solution was determined. The study was carried out with the Shadow Sizing method. The results were subjected to statistical analysis and the surface area of the response of the relation between the time and temperature of sedimentation and the number of particles which stay in the solution was calculated. The research results proved that the temperature significantly affects the cleaning degree of solutions by sedimentation and its duration. After sedimentation in solutions, particles with the surface area from 0.001-0.003 mm2 remain. Those particles are not subject to sedimentation and constitute a coloidal suspension in the solution.